2015
DOI: 10.1155/2015/493710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Additives on the Flammability and Mechanical Properties of Intumescent Flame Retarded Polypropylene Compounds

Abstract: The effect of particle size reduction of the components of a common intumescent flame retardant system, consisting of pentaerythritol (PER) and ammonium polyphosphate (APP) in a weight ratio of 1 to 2, was investigated on the flammability and mechanical performance of flame retarded polypropylene (PP) compounds. Additives of reduced particle size were obtained by ball milling. In the case of PER, the significant reduction of particle size resulted in inferior flame retardant and mechanical performance, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…3b improved better in TM but decreased in TS. The presence of APP which caused a decrease as expected agrees with the report of Bocz et al [17]. Similar trend have been reported for OPFC as seen in the work of Khalili et al [9], Redwan et el [18] and Norzali et al [19].…”
Section: Tensile Propertiessupporting
confidence: 90%
“…3b improved better in TM but decreased in TS. The presence of APP which caused a decrease as expected agrees with the report of Bocz et al [17]. Similar trend have been reported for OPFC as seen in the work of Khalili et al [9], Redwan et el [18] and Norzali et al [19].…”
Section: Tensile Propertiessupporting
confidence: 90%
“…Utilizing the physical blends of various FR components as IFR was advantageous for the sake of convenience. However, it was reported that the size and its distribution of each component in the substrate significantly affected the performance of both FR and mechanical property (56). The main reason was that the functional compositions could not come into contact with each other sufficiently, which was the disadvantage compared with the chemical bonding process.…”
Section: Loi and Ul-94 Vertical Burning Testsmentioning
confidence: 99%
“…However, it was found that its distribution and the size of each component in the substrate significantly affected the performance both of FR and mechanical property. [8] The main reason was that the functional compositions could not contact with each other sufficiently. It was a disadvantage compared with the chemical bonding process.…”
Section: Samplesmentioning
confidence: 99%
“…Consequently, the occurrence of smoke in combustion is effectively suppressed. For these advantages, IFRs are widely applied to different polymer matrix including polypropylene (PP), [8,9] polycarbonate (PC), [10] polyurethane (PU), [1,11,12] and epoxy resin (EP), [5,13,14] and so forth. Although the distinct flame retardant effect has been achieved, there are still many shortcomings including easy migration, poor durability, and water solubility of IFRs, by far many endeavors have been dedicated to overcome these drawbacks.…”
Section: Introductionmentioning
confidence: 99%